Gangguan Kepribadian - Fadilah, Risydah; Fitri, Dira Zahara; Febriani, Melisa; Murni, Sheila Natasya (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out about a person's personality disorder, whether they have this personality disorder from an early age (congenital) or because of stress in dealing with life. Personality disorders are usually caused by the process of mental development and social life. Personality disorders themselves are processes of mental development that are not in accordance with mental development in general or can be called mental disorders. Personality disorder is a condition of someone who has unhealthy thought patterns or behavior. However, this disorder can be cured with therapy or using medication if it is too severe.